El problema de la estabilidad normativa en la filosofía política de John Rawls - Alútiz, Juan Carlos (Política y Sociedad, 2008)
The problem of stability in every normative theoretical model refers, in the first place, to questions such as the legitimacy of the social organization principles, and secondly, to the moral motivation to acknowledge them and rule personal behaviour with them. These two questions are confronted by Rawls in a very different manner in his two main works of reference: from an internal standpoint in Theory of the Justice, and from more of an external outlook in Political Liberalism. The objective of this article is an indepth analysis of the epistemologic foundation inasmuch as the practical implications of these two diverse points of view